Assessment of Hyperactive Reflexes in Patients with Spinal Cord Injury. (15th January 2015) - Xu, Dali; Guo, Xin; Yang, Chung-Yong; Zhang, Li-Qun
Abstract : Hyperactive reflexes are commonly observed in patients with spinal cord injury (SCI) but there is a lack of convenient and quantitative characterizations. Patellar tendon reflexes were examined in nine SCI patients and ten healthy control subjects by tapping the tendon using a hand-held instrumented hammer at various knee flexion angles, and the tapping force, quadriceps EMG, and knee extension torque were measured to characterize patellar tendon reflexes quantitatively in terms of the tendon reflex gain (G tr ), contraction rate (R c ), and reflex loop time delay (t d ). It was found that there are significant increases in G tr and R c and decrease in t d in patients with spinal cord injury as compared to the controls (P < 0.05 ). This study presented a convenient and quantitative method to evaluate reflex excitability and muscle contraction dynamics. With proper simplifications, it can potentially be used for quantitative diagnosis and outcome evaluations of hyperreflexia in clinical settings.